Composite 3D printing of biomimetic human teeth - A. J. Cresswell-Boyes; G. R. Davis; M. Krishnamoorthy; D. Mills; A. H. Barber (Scientific Reports, 2022)
Abstract Human teeth are mechanically robust through a complex structural composite organisation of materials and morphology. Efforts to replicate mechanical function in artificial teeth (typodont teeth), such as in dental training applications, attempt to replicate the structure and morphology of real teeth but lack tactile similarities during mechanical cutting of the teeth. In this study, biomimetic typodont teeth, with morphology derived from X-ray microtomography scans of extracted teeth, were 3D printed using an approach to develop novel composites. These composites with a range of glass, hydroxyapatite and porcelain reinforcements within a methacrylate-based photopolymer resin were compared to six commercial artificial typodont teeth. Mechanical performance of the extracted human teeth and 3D printed typodont teeth were evaluated using a haptic approach of measuring applied cutting forces. Results indicate 3D printed typodont teeth replicating enamel and dentine can be mechanically comparable to extracted human teeth despite the material compositions differing from the materials found in human teeth. A multiple parameter variable of material elastic modulus and hardness is shown to describe the haptic response when cutting through both human and biomimetic, highlighting a critical dependence between the ratio of material mechanical properties and not absolute material properties in determining tooth mechanical performance under the action of cutting forces.